Analysis Of Geography Planning and Village Funds to Improve Development Program - Zulfida, Ida; Situmeang, Mahyudin; Reis, Cristovao (JURNAL GEOGRAFI, 2023)
Geography planning is an essential element in the creation of a plan. Planners develop a method by analyzing data and identifying goals for the community or the development project. This study aims to analyze how planners or governments analyze geography planning and village funds to improve development programs. This research type is quantitative”data collection techniques using a closed questionnaire with a Likert scale model and interviews. The population and sample of the study were 47 people. The analysis technique was carried out by processing data collected from respondents, grouping data based on the type of respondent, making tabulations, and carrying out statistical test calculations. The results of this study found that the Village is a geographical manifestation caused by socio-economic, political, and cultural physiographical elements. Geographical planning analysis and village funds are intended for villages with each village planning village development needs. Support for geographic planning analysis and village funds can be seen from the achievement of policy aspects such as agenda setting, policy formulation, policy adoption, policy implementation, and policy evaluation in villages with a low relationship with effectiveness. From development programs. Public services to the point of development programs have an intense relationship, and the accountability dimension is classified as moderate. Productivity dimensions, service quality responsiveness, and responsibility for the development program's effectiveness. The policy on the simultaneous use of village funds and public services on the effectiveness of development programs has a strong relationship of 72.25. However, this study did not examine a low correlation of 0.27.36%.Keywords: Village, Policy, Public, Geography, Planning